Managerial Ability And Earnings Management: Moderating Role Of Risk-Taking Behavior - Sulhendri; Simamora, Alex Johanes; Nicko Albart; Sri Adella Fitri; Listiana Sri Mulatsih (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
Examining how risk-taking behaviour affects managerial skills and earnings management is the goal of this study. The study's sample consists of 846 manufacturing companies listed on the Indonesian Stock Exchange between 2008 and 2018. Data envelopment analysis is a proxy for managerial skill. Accruals and actual earnings management are two aspects of earnings management. The firm fixed-effect regression is used in data analysis. The influence of managerial skills on earnings management is mitigated by risk-taking behaviour. Capable managers are more likely to use their propensity for risk-taking to manipulate earnings. Capable managers respond to earnings volatility resulting from risk-taking by implementing earnings management strategies. This study closes the gap left by earlier research and offers fresh proof of risk-taking behaviour that helps identify situations where managers use their expertise to control profits.